The new shares market: regulatory intervention, forecast errors and challenges - Ramadilli Mohd, Shamsher Mohamad (2003)
A new issue is defined under Malaysian laws as the sale of unissued ordinary shares out of a previously closely held firm's authorised number of shares. Offers of existing issued shares are defined as sale of shares. Private placements, which are direct sale of unissued shares to designated investors, are permitted in limited cases and account for 5 to 10percent of funds per year in the market. Therefore, the phrase 'new issues' has a restricted meaning in this country, and is consistent with the meaning of initial public offerings (or IPOs) of private companies and government-linked enterprises.